(Non-)Insurance Markets, Loss Size Manipulation and Competition - Experimental Evidence - Jeroen Hinloopen; Adriaan R. Soetevent (Tinbergen Institute, 2016)
The common view that buyer power of insurers may effectively counteract provider market power critically rests on the idea that consumers and insurers have a joint interest in extracting price concessions. However, in markets where the buyer is an insurer, the interests of insurers and consumers to reduce prices may be importantly misaligned. The positive dependence between loss size and the insurer's expected profits limits the insurer's incentives to reign in loss sizes; in markets with small initial loss sizes, insurers may try to raise these in order to create demand for insurance. After having defined insurance and non-insurance markets based on the initial loss size, we develop theory to show that insurers with buyer power have incentives to create insurance markets. Insurer competition will push their profits to zero but markets do not return to the initial non-insurance state. This constitutes a welfare loss. We design experimental insurance markets to test our theory and find support. Monopolistic insurer-subjects in non-insurance markets increase loss sizes to establish insurance markets. Insurer competition eliminates profits but not the loss size to uninsured consumers. This provides an additional reason to be careful in granting insurers buyer power.
Keywords: C92; D81; G22; I11; L13; 330; insurance markets; risk elicitation; experiment; buyer power